Molecular identification and genetic diversity analysis of Cryptosporidium spp. infecting dogs from central and northern Jordan: Detection of zoonotic genotype IId. - Rami M Mukbel; Eman M Etoom; Haifa B Hammad; Heidi L Enemark; Marwan M Abu Halaweh (PLoS ONE)
Cryptosporidium spp. are common causes of gastrointestinal disease in both humans and animals. This was a cross-sectional study conducted to determine the infection rate and genetic characteristics of Cryptosporidium infecting dogs in Jordan. A total of 249 faecal samples were collected from stray, pet, and breeding dogs from kennels (independent of their clinical condition) across three governorates in Jordan (Amman and Zarqa in Central Jordan and Irbid in Northern Jordan). Faecal samples were screened for Cryptosporidium using polymerase chain reaction (PCR) targeting the 18S rRNA gene, revealing an overall infection rate of 18.9% (47 out of 249). Cryptosporidiosis was significantly associated with indoor dogs, dogs cohabiting with other animals, and consuming raw food. Among the successfully sequenced samples, 25 (58.1%) were Cryptosporidium canis, 15 (34.9%) were Cryptosporidium parvum, and three (7.0%) were Cryptosporidium baileyi. Multiple diversity tests were employed, indicating low genetic differentiation between the studied populations of C. parvum and C. canis. Stability was observed for C. parvum, with minimal expansion observed for C. canis. Notably, each species exhibited a single dominant haplotype, consistent with the AMOVA results, where most of the variability occurred within populations. Further genotyping of C. parvum and C. canis was conducted by sequencing the gp60 gene. C. parvum isolates worldwide displayed solely the zoonotic IId genotypes, namely, IIdA20G1, IIdA22G1, IIdA18G1, and IIdA19G1. In contrast, the C. canis isolates exhibited the animal subtypes XXe and XXd. Consequently, dogs may serve as a source of infection with C. parvum and pose a public health risk in Jordan.